Diagnostic value of N-terminal ProB-Type Natriuretic Peptide in Emergency Department: Analysis by subgroups - P. Villa; A. Dolci; R. Dominici; M. Panteghini; C. Fundarò; S. Guzzetti (Emergency Care Journal, 2012)
Objectives. Our aim was to evaluate the diagnostic impact of N-terminal pro B-type natriuretic peptide (NT-proBNP) measurement in patients presenting with acute dyspnea in Emergency Department (ED), taking into account clinical and chest x-ray results routinely obtained. Methods. This was a prospective observational study. Four hundred eighty-eight consecutive subjects evaluated for dyspnea in a metropolitan 600 beds hospital ED, entered into the final data analysis. According to a clinical and radiological score, the patients enrolled were divided in three groups: low (A-group), intermediate (B-group), and high (C-group) probability of heart failure. Results. NT-proBNP median value was 2445 ng/L (Inter Quartile Range 631-5847 ng/L), and the area under the receiver-operating characteristic curves (AUC) was 0.854 for NT-proBNP, 0.921 for clinical/radiological score and 0.936 for the two in combination (logistic model). In the B-group (intermediate) NT-proBNP test added correct diagnostic information in 126 subjects with HF and in 53 subjects without a final diagnosis of HF. In A- and C-group NT-proBNP test added correct diagnostic information in 1 patient. Conclusions. NT-proBNP did not substantially enhance diagnostic accuracy in all patients with shortness of breath in ED. However, in patients with not conclusive clinical and radiological results NT-proBNP determinations improved the percentage of correct diagnosis.